1993
DOI: 10.3109/00365519309086621
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine induces β-adrenergic desensitization and differentiation of HL-60 cells

Abstract: The HL-60 cell line was cultured in a serum-free medium and exposed to various concentrations of EPI. The effects on cell growth, differentiation and beta-adrenergic response were followed during the culture period of 72 h. Short-term exposure (3 min) to EPI (1 nM-1 mM) in the presence of theophylline (4 mM) caused a dose-dependent increase of cAMP levels with a maximum of 1500% above basal levels. When the cells were exposed to EPI (1 nM-10 microM) for 72 h, a dose-dependent increase of cAMP levels with a max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
1

Year Published

1994
1994
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
1
1
Order By: Relevance
“…Already relatively small 2 The method used does not allow us to obtain absolute values for cellular cAMP levels. However, previous studies in granulocytes have demonstrated basal cAMP levels of 1-3 pmol/106 cells (Prytz et al, 1991;Bang et al, 1993 Thus, our data demonstrate that cAMP blocks CD4 endocytosis, as 1) all compounds that raised cAMP blocked CD4 endocytosis and 2) there was an all-over relationship between the cAMP levels and the inhibition of CD4 endocytosis. We next investigated whether the physiological receptor agonist PGE1, which is known to raise cAMP myeloid cells (Scott, 1970;Bourne et al, 1971), also had effects on CD4 endocytosis.…”
Section: Cd4 Intemnalization In Hl-60 Cellssupporting
confidence: 61%
“…Already relatively small 2 The method used does not allow us to obtain absolute values for cellular cAMP levels. However, previous studies in granulocytes have demonstrated basal cAMP levels of 1-3 pmol/106 cells (Prytz et al, 1991;Bang et al, 1993 Thus, our data demonstrate that cAMP blocks CD4 endocytosis, as 1) all compounds that raised cAMP blocked CD4 endocytosis and 2) there was an all-over relationship between the cAMP levels and the inhibition of CD4 endocytosis. We next investigated whether the physiological receptor agonist PGE1, which is known to raise cAMP myeloid cells (Scott, 1970;Bourne et al, 1971), also had effects on CD4 endocytosis.…”
Section: Cd4 Intemnalization In Hl-60 Cellssupporting
confidence: 61%
“…Theophylline, caffeine and isobutylmethylxanthine act as non-specific inhibitors of phosphodiesterase isoenzymes (Nicholson et al 1991 Previous studies in our laboratory have demonstrated a reduction in the expression of the nuclear oncogenes, c-fos and c-myc in HL-60 cells, after exposure to theophylline and theophylline plus isoproterenol (Moens et al 1990). We have also observed a modest degree of HL-60 cell differentiation after cAMP stimulation through P-adrenergic receptors (Bang et al 1993). The cGMP levels in this study were, however, not measured.…”
contrasting
confidence: 48%
“…4 In addition, in vivo administration of the 1 agonist isoprenaline in rat resulted in a suppression of the growth of the C-6 glioma tumour,' while ablation of the sympathetic nerve system augmented tumour growth.5 Furthermore, this suppressive response of isoprenaline was proportional to the 1 adrenergic receptor density on the tumour cell surface.6 Reduced density of 13 adrenergic receptors in tumour tissue has been previously reported in in vitro studies. Mouse lymphocytic leukaemia cells have been shown to have fewer 1 adrenoceptors per cell and a smaller fraction of these receptors are functionally active cell surface receptors.7 In lung, mouse neoplastic cells contained fewer 1 adrenoceptors and produced less cAMP in response to isoprenaline.8 In human lung in vitro 13 receptors were also decreased in cancer tissue.…”
mentioning
confidence: 85%